2013
DOI: 10.1016/j.jaut.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation study suggests epigenetic accessibility and transcriptional poising of interferon-regulated genes in naïve CD4+ T cells from lupus patients

Abstract: Systemic lupus erythematosus is an autoimmune disease characterized by multi-system involvement and autoantibody production. Abnormal T cell DNA methylation and type-I interferon play an important role in the pathogenesis of lupus. We performed a genome-wide DNA methylation study in two independent sets of lupus patients and matched healthy controls to characterize the DNA methylome in naïve CD4+ T cells in lupus. DNA methylation was quantified for over 485,000 methylation sites across the genome, and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
215
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 291 publications
(236 citation statements)
references
References 17 publications
(23 reference statements)
15
215
1
1
Order By: Relevance
“…STAT1 in particular has been associated with the development of, for example, lupus nephritis (Dong et al, 2007) and purpose anaemia (DominguezGutierrez et al, 2014) and also has been shown to be hypomethylated in CD4+ T-cells from lupus patients (Coit et al, 2013) as well as having higher expression in peripheral blood mononuclear cells (PBMCs) from SLE patients (Karonitsch et al, 2009). Our results show that the synergism observed between IFN-α and AdMP on inflammation is likely to be mediated by a readily increased phosphorylation and therefore higher transcriptional activity of STAT1.…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 in particular has been associated with the development of, for example, lupus nephritis (Dong et al, 2007) and purpose anaemia (DominguezGutierrez et al, 2014) and also has been shown to be hypomethylated in CD4+ T-cells from lupus patients (Coit et al, 2013) as well as having higher expression in peripheral blood mononuclear cells (PBMCs) from SLE patients (Karonitsch et al, 2009). Our results show that the synergism observed between IFN-α and AdMP on inflammation is likely to be mediated by a readily increased phosphorylation and therefore higher transcriptional activity of STAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Although early studies reported elevated levels of IFN- in sera of SLE patients, the sensitivity of the method appears low, since IFN-I levels are either undetectable or dependent on several factors such as ethnic background, age, and sex (143)(144)(145)(146). Indirect methods were also used to measure IFN-I activity.…”
Section: Measuring Interferon Activity In Patientsmentioning
confidence: 99%
“…Recent studies applying sequence analysis technology have gained meaningful results that provide us with more information about lupus heritability [79], ethnicity variance [80] and renal involvement with DNA methylome analysis in CD4+ T cells [81]. Coit et al confirmed a group of interferon-related genes that are aberrantly hypomethylated, including IFN-induced protein 44-like (IFI44L), IFN-induced protein with tetratricopeptide (IFIT1), IFIT3, MX dynamin-like GTPase 1 (MX1), signal transducer and activator of transcription 1 (STAT-1), bone marrow stromal cell antigen 2 (BST2) and tripartite motif containing 22 (TRIM22), in lupus CD4+ T cells [82]. Furthermore, a newly identified IFN-related gene IFI44L has been deciphered in SLE, and the study also emphasized its potential role as a diagnostic biomarker [83].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%